Sustainability of Urban Regeneration Projects in Resilient Cities: a Multiple Case Study - Alessandra Ricciardelli; Nicola Raimo; Francesco Manfredi; Filippo Vitolla (16th International Forum on Knowledge Asset Dynamics - Proceedings: Managing Knowledge in Uncertain Times Distribution – Rome, Italy 1-3 September 2021, 2021)
In recent years, the integration of sustainability principles in urban planning has become increasingly important. The growing attention to economic, social and environmental aspects is also influencing the practice and policy of urban regeneration. In particular, the search for new ways to regenerate cities in a sustainable way has led to the concept of sustainable urban regeneration. However, despite the relevance of this concept, only a few contributions have quantitatively examined the actual sustainability outcomes of different urban regeneration interventions. This study aims to fill this important gap by examining the level of sustainability of urban regeneration interventions in the Apulian context. The results of the multiple case study analysis show a high level of sustainability of the interventions in all three contexts examined. However, they show some weaknesses related mainly to the absence of strategies aimed at the inclusion of women in the labour market and to the low efficiency in the use of energy. The results offer important implications and guidelines for municipalities implementing urban regeneration projects.
Keywords: 330; Urban regeneration; Urban sustainability; Sustainable urban regeneration; Sustainability indicators; Apulia